Are increased salivary carbonic anhydrase VI levels related to the amount of supragingival dental calculus formation and clinical periodontal scores? - Taner Arabacı; Yasin Çiçek; Şükrü Beydemir; Cenk Fatih Çanakçı; Varol Çanakçı (Elsevier, 2015)
Background/purpose: Carbonic anhydrase (CA) VI is a unique salivary isoenzyme that regulates the pH in the oral environment. Its increased levels result in a more-alkaline saliva, hence it was hypothesized to contribute to dental calculus formation together with salivary inorganic salts. In this study, we evaluated the relationship between salivary CA VI levels and the amount of supragingival dental calculus formation on human teeth. Materials and methods: Seventy-five volunteers were grouped according to their oral hygiene status, and the amount of supragingival dental calculus was measured by the Volpe-Manhold Index (VMI). Group I included control individuals who had no dental calculus formation clinically (VMI = 0). Group II included light calculus formers (VMI < 7), and group III included heavy calculus formers (VMI ≥ 7). Clinical periodontal indices and salivary CA VI levels were measured in all individuals, and were compared among the groups and correlated within groups. Results: Differences among the groups according to clinical scores and CA VI levels were found to be statistically significant (P < 0.05). The correlation between the oral hygiene index and salivary CA VI levels was found statistically significant in group III (P < 0.05), but was not statistically significant in group II (P > 0.05). Significant positive correlations were found between salivary CA levels and amount of dental calculus in groups II and III (P < 0.05 and < 0.01, respectively). Conclusion: This study found positive correlations between increased salivary CA VI activity and the amount of supragingival dental calculus; however, further investigations are needed to clarify the exact association between these parameters.